Evaluating the impact of different afforestation timescales on the soil quality in a typical watershed valley using the criteria importance through intercriteria correlation method and gray target model - Yin, Huiyan; Yu, Bo; Zhang, Zhiwei; Jia, Lizhi; Xue, Jie; Chen, Xiaoqiang; Wang, Shunke; Han, Jiahua; Xing, Zhen (Frontiers in Forests and Global Change, 2022)
Soil quality evaluation is the foundation for understanding the current situation of soil quality and promoting the sustainable utilization of land resources. However, the evaluation of the impacts of the different long-term afforestation timescales on the soil quality in a typical watershed valley area is still insufficient. Here, based on the soil samples collected from different afforestation years of 2, 5, 11, 15 and 31 years and natural sample plots with similar site conditions in the same region, the grey target model and Criteria Importance Though Intercriteria Correlation (CRITIC) method are used in this study to evaluate the soil quality of the sample plots with different afforestation years and the corresponding natural sample plots in the Tibet Plateau. Results show that: (1) The most positive soil physical and chemical indexes increase with the increase in afforestation years based on the analysis of the characteristics, variation, and fertility grade of 13 soil physical and chemical indexes in different areas. The content of most soil physical and chemical indexes is greater than that in the corresponding natural sample plots in 31 years of afforestation. (2) The target degree of the soil quality in the study area is divided into five grades according to the principle of equal division and integration. The soil quality grade of the corresponding sample plot after 15 years of afforestation is grade 4. The other plots are grade 5. (3) The soil quality index (SQI) generally increases with the increase of in forestation years. The different afforestation years indicate SQI (0.709) of 15 years > SQI (0.662) of 31 years > SQI (0.426) of 11 years > SQI (0.348) of 2 years> SQI (0.309) of 5 years. (4) The full data set method verifies the effectiveness of the grey target model. The two soil quality evaluation methodologies are consistent and can verify each other’s accuracy. The correlation coefficient of the two results reaches 0.957. This study finds that the long-term afforestation timescales have improved the soil quality of watershed valley. Available phosphorus, silt, soil water content are the main factors impacting the soil quality in the afforestation timescales.